Adherence to the Mediterranean Diet as a Modifiable Risk Factor for Thyroid Nodular Disease and Thyroid Cancer: Results From a Pilot Study - Barrea, Luigi; Muscogiuri, Giovanna; Alteriis, Giulia de; Porcelli, Tommaso; Vetrani, Claudia; Verde, Ludovica; Aprano, Sara; Fonderico, Francesco; Troncone, Giancarlo; Colao, Annamaria; Savastano, Silvia (Frontiers in Nutrition, 2022)
Iodine deficiency is the most important established nutritional risk factor for the development of thyroid nodular disease. Nevertheless, to the best of our knowledge, to date no study focused on the association between the adherence to the Mediterranean diet (MD) and thyroid nodular disease. Adherence to the MD was evaluated using the PREvención con DIetaMEDiterránea (PREDIMED) questionnaire. Physical activity, smoking habits, and anthropometric parameters were studied. PREDIMED was used to evaluate the degree of adherence to the MD. Evaluation of fine needle aspiration cytology of thyroid lesions based on 2013 Italian thyroid cytology classification system. Cytology of thyroid nodules was carried out through sonography-guided fine-needle aspiration and patients were divided into 5 categories: TIR2, TIR3a, TIR3b, TIR4, and TIR5. The study population consisted of 794 subjects (554 females, 69.8%), aged 18–65 years, with BMIs ranging from 19.4 to 55.3 kg/m2. Thyroid nodular disease was present in 391 participants (49.2%), and the most frequent cytological categories was TIR2 (18.3 %), followed by a TIR4 (8.9 %). The presence of thyroid nodules was also significantly associated with the lowest adherence to the MD (OR 6.16, p<0.001). Patients with TIR5 had the lower adherence to the MD (2.15±1.12 score) compared to other TIRs (p<0.001). The cytological category with high-risk of malignancy (TIR4/TIR5) was significantly associated with the lowest adherence to the MD (OR 137.55, p<0.001) and PREDIMED score (OR= 0.33, p<0.001, 95% IC=0.26–0.41, R2=0.462). At multiple regression analysis, PREDIMED score was the main predictor of both the presence of nodules (p<0.001) and the cytological category with high-risk of malignancy (p<0.001). At ROC analysis PREDIMED score ≤ 5 and ≤ 4 (p=0.001) were the values that predicted the presence of thyroid nodular disease and cytological category with high-risk of malignancy, respectively. In conclusion, our study demonstrated that the low adherence to the MD is associated with the presence of thyroid nodular disease and in particular with those at high-risk of malignancy.